Negative regulation of sigma 54-dependent dctA expression by the transcriptional activator DctD. - Labes, M (1993)
In Rhizobium meliloti, the presence of the C4-dicarboxylate transport protein DctA is required for symbiotic N2 fixation in alfalfa root nodules. Expression of dctA is inducible and is mediated by a sensor and activator gene pair encoded by dctB and dctD. In the presence of C4-dicarboxylates, the DCTB sensor protein is believed to phosphorylate and activate DCTD, which in turn activates transcription at the sigma 54-dependent dctA promoter. Here, we present evidence that in addition to activating dctA transcription, DCTD can also repress expression of dctA. By employing an ntrC allele, ntrC283, whose product appears to activate dctA transcription independently of DCTD, we found that while ntrC283 leads to constitutive dctA expression in the absence of dctB and dctD, in a dctB+ dctD+ ntrC283 background high-level expression of dctA occurred in succinate but not in glucose-grown cells. This result suggested that in uninduced cells, inactive DCTD binds to the dctA promoter and prevents its activation by NTRC283. Consistent with the latter interpretation was the observation that overexpression of DCTD from a plasmid promoter prevents dctA expression and results in a Dct- phenotype. Moreover the Dct- phenotype resulting from the overexpression of dctD was dominant to ntrC283. Results from studies of the ability of ntrC283 to suppress the Dct- phenotype of dctB alleles, together with the finding that the Fix- phenotype of a particular dctB allele was dctD dependent, suggest that in particular dctB alleles, sufficient dctD transcription occurs such that the resulting inactive DCTD prevents activation of dctA transcription by NtrC283 or alternate symbiotic regulators. The latter suggestion is supported by the observation that in symbiosis, R. meliloti strains in which DCTD was overexpressed formed nodules which failed to fix nitrogen.